Selective Internal Radiation Therapy for Liver Metastasis of Papillary Thyroid Carcinoma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Papillary carcinoma of thyroid (PTC) is the most common neoplasm of the thyroid gland that usually invades lymphatics rather than blood vessels. Hematogenous metastasis of PTC is rare, and distant metastasis to the liver is even rarer. Selective internal radiation therapy with Y-90 microspheres is a well-recognized technique in the treatment of liver metastases. Herein, we present a case of PTC with radioactive iodine-negative hepatic metastasis detected by F-18-FDG PET/CT and treated with selective internal radiation therapy.
Keywords: papillary thyroid carcinoma; liver metastasis; F-18-FDG PET/CT; selective internal radiation therapy; Y-90; RADIOEMBOLIZATION; Y-90